Regulation of UCP1 in the Browning of Epididymal Adipose Tissue by β3-Adrenergic Agonist: A Role for MicroRNAs - Zongji Zheng; Xiaomeng Liu; Qianwei Zhao; Lei Zhang; Chenzhong Li; Yaoming Xue (International Journal of Endocrinology)
Background. White adipose tissue browning may be a promising strategy to combat obesity. UCP1 is strongly induced in White adipose tissue with β3-adrenergic agonist treatment, but the causes of this increase have not been fully elucidated. This study aims to explore more miRNAs involved in the process of browning of visceral adipose tissue. Methods. Total of fourteen mice were randomly divided into control and study group. Study group mice were injected intraperitoneally with CL316243 once daily for seven days; meanwhile the control group were treated with 0.9% NaCl. After a 7-day period, the expression of genes involved in WAT browning and potential UCP1-targeting miRNAs in adipose tissues was analyzed by qPCR. Results. qPCR analysis revealed that UCP1, DIO2, CIDEA, and CPT1B in epididymal adipose tissue were overexpressed in CL316243 group. Furthermore, potential UCP1-targeting miR-9 and miR-338-3p in epididymal adipose tissue were significantly decreased in CL316243 group. Conclusion. This suggests that potential UCP1-targeting miR-9 and miR-338-3p may be involved in the browning of epididymal adipose tissue by regulating UCP1 gene expression. In this study, we demonstrated that this increase of UCP1 is due, at least in part, to the decreased expression of certain UCP1-targeting miRNAs in epididymal adipose tissue compared to control.